Sự phân bố serotype virus Dengue ở bệnh nhân tại bệnh viện Trung ương Huế - Liên, Nguyễn Thị Nam; Hòa, Nguyễn Văn; Dung, Châu Thị Mỹ; Hồng, Phan Nữ Diệu; Thủy, Nguyễn Thị Thu (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.